Mining the Drilosphere: Bacterial Communities and Denitrifier Abundance in a No-Till Wheat Cropping System - Schlatter, Daniel C.; Reardon, Catherine L.; Johnson-Maynard, Jodi; Brooks, Erin; Kahl, Kendall; Norby, Jessica; Huggins, David; Paulitz, Timothy C. (Frontiers in Microbiology, 2019)
Earthworms play important roles in no-till cropping systems by redistributing crop residue to lower soil horizons, providing macropores for root growth, increasing water infiltration, enhancing soil quality and organic matter, and stimulating nitrogen cycling. The soil impacted by earthworm activity, including burrows, casts, and middens, is termed the drilosphere. The objective of this study was to determine the effect of earthworms on soil microbial community composition in the drilosphere at different landscape slope positions. Soil cores (50 cm depth) were extracted from three landscape locations (top, middle and bottom slope positions) on a sloping aspect of a no-till wheat farm. Soil was sampled at the bottom of the soil core from inside multiple earthworm (Lumbricus terrestris) channels (drilosphere) and from adjacent bulk soil. Bacterial communities were characterized for 16S rRNA gene diversity using high-throughput sequencing and functional denitrifier gene abundance (nirK, nirS and nosZ) by quantitative PCR. Bacterial communities were structured primarily by the landscape slope position of the soil core followed by source (bulk versus drilosphere soil), with a significant interaction between core position and source. The families AKIW874, Chitinophagaceae, and Comamonadaceae and the genera Amycolatopsis, Caulobacter, Nocardioides, and Variovorax were more abundant in the drilosphere compared to the bulk soil. Most of the individual bacterial taxa enriched in the drilosphere versus bulk soil were members of Actinobacteria, including Micrococcales, Gaiellaceae, Solirubrobacterales, and Mycobacterium. In general, the greatest differences in communities were observed in comparisons of the top and bottom slope positions in which the bottom slope communities had statistically significantly greater richness, diversity, and denitrifier abundance than the top slope position. Populations of denitrifiers(i.e. ratio of nirK+nirS to 16S rRNA) were more abundant in earthworm-impacted soils and there was a significant impact of L. terrestris on soil community composition was observed only in the top landscape position. There were significant correlations between the abundance of nirK and nirS and taxa within Proteobacteria, Acidobacteria, Actinobacteria, Verrucomicrobia, and Chloroflexi, suggesting a broad diversity of denitrifying bacteria. Earthworms influence the soil microbial communities, but the impact depends on the slope location in a variable landscape, which likely reflects different soil characteristics.